The role of cultural mega events in the enhancement of city’s image attributes: differences between engaged and attendee participants - Santos, J. Freitas (2014)
In a time of fierce competition between regions, an image serve as a basis to develop a strong sense of community, which fosters trust and cooperation that can be mobilized for regional growth. A positive image and reputation could be used in the promotional activities of the region benefiting all the stakeholders as a whole. Mega cultural events are frequently used to attract tourists and investments to a region, but also to enhance the city’s image. This study adopts a marketing/communication perspective of city’s image, and intends to explain how the image of the city is perceived by their residents. Specifically, we intend to compare the perceptions of residents that effectively participated in the Guimarães European Capital of Culture (ECOC) 2012 (engaged residents), and the residents that only assisted to the event (attendees). Several significant findings are reported and their implications for event managers and public policy administrators presented, along with the limitations of the study.